Associations and Impact Factors between Living Arrangements and Functional Disability among Older Chinese Adults - Wang, Hui (Public Library of Science, 2013)
OBJECTIVES: To examine the association of living arrangements with functional disability among older persons and explore the mediation of impact factors on the relationship. DESIGN: Cross-sectional analysis using data from Healthy Aging study in Zhejiang Province. PARTICIPANTS: Analyzed sample was drawn from a representative rural population of older persons in Wuyi County, Zhejiang Province, including 1542 participants aged 60 and over in the second wave of the study. MEASUREMENTS: Living arrangements, background, functional disability, self-rated health, number of diseases, along with contemporaneous circumstances including income, social support (physical assistance and emotional support). Instrument was Activities of Daily Living (ADL) scale, including Basic Activities Daily Living (BADL) and Instrumental Activities of Daily Living (IADL). RESULTS: Living arrangements were significantly associated with BADL, IADL and ADL disability. Married persons living with or without children were more advantaged on all three dimensions of functional disability. Unmarried older adults living with children only had the worst functional status, even after controlling for background, social support, income and health status variables (compared with the unmarried living alone, ß for BADL: −1.262, ß for IADL: −2.112, ß for ADL: −3.388; compared with the married living with children only, ß for BADL: −1.166, ß for IADL: −2.723, ß for ADL: −3.902). In addition, older adults without difficulty in receiving emotional support, in excellent health and with advanced age had significantly better BADL, IADL and ADL function. However, a statistically significant association between physical assistance and functional disability was not found. CONCLUSION: Functional disabilities vary by living arrangements with different patterns and other factors. Our results highlight the association of unmarried elders living with children only and functioning decline comparing with other types. Our study implies policy makers should pay closer attention to unmarried elders living with children in community. Community service especially emotional support such as psychological counseling is important social support and should be improved.